2023
DOI: 10.1186/s40478-023-01512-1
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Creutzfeldt–Jakob disease infected human cerebral organoids retain the original human brain subtype features following transmission to humanized transgenic mice

Abstract: Human cerebral organoids (COs) are three-dimensional self-organizing cultures of cerebral brain tissue differentiated from induced pluripotent stem cells. We have recently shown that COs are susceptible to infection with different subtypes of Creutzfeldt–Jakob disease (CJD) prions, which in humans cause different manifestations of the disease. The ability to study live human brain tissue infected with different CJD subtypes opens a wide array of possibilities from differentiating mechanisms of cell death and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…These 3D models can be infected with different subtypes of Creutzfeldt-Jakob disease (CJD) prions, which in humans cause different manifestations of the disease, maintaining the original subtype characteristics of the infecting prions. Mouse models expressing human prion proteins inoculated either with cerebral organoids that had been infected with two CJD subtypes (MV1 and MV2) or with the original human brain material present similar disease characteristics, demonstrating that this in vitro model can faithfully reproduce different subtypes of prion disease [68,113].…”
Section: Creutzfeldt-jakob Disease (Cjd)mentioning
confidence: 86%
“…These 3D models can be infected with different subtypes of Creutzfeldt-Jakob disease (CJD) prions, which in humans cause different manifestations of the disease, maintaining the original subtype characteristics of the infecting prions. Mouse models expressing human prion proteins inoculated either with cerebral organoids that had been infected with two CJD subtypes (MV1 and MV2) or with the original human brain material present similar disease characteristics, demonstrating that this in vitro model can faithfully reproduce different subtypes of prion disease [68,113].…”
Section: Creutzfeldt-jakob Disease (Cjd)mentioning
confidence: 86%
“…Tg33 mouse brains were screened by RT-QuIC assay (methods below) for the presence of prion seeding activity. Most tg66 mouse brains were screened for neuropathology (H&E sections) and IHC demonstration of prion deposition consistent with prion disease using antiprion antibody 3F4 as described [32]. A small subset of tg66 mice that did not have formalin fixed tissue available were screened by RT-QuIC assay (methods below) for prion seeding activity rather than neuropathology.…”
Section: Confirmation Of Prion Infectionmentioning
confidence: 99%
“…We have previously shown that human cerebral organoids (COs) can be infected with sCJD prions and faithfully propagate the original inoculum [ 21 , 22 ]. The infection could be reduced by treatment with PPS either administered before and during infection or after establishment of infection, supporting the use of the organoid model for screening putative therapeutic strategies [ 23 ].…”
Section: Introductionmentioning
confidence: 99%